Be explicit: Defining the difference between the Office of Diversity & Inclusion and the Office of Diversity & Equity. (2nd December 2019) - McCleary-Gaddy, Asia
Abstract: Diversity, inclusion, and equity are recognized as educational priorities and strategies for excellence across medical education. However, an inadvertent consequence of this push for best practice is that these terms are used interchangeably. This personal view intends to highlight the importance of language in an office of diversity and how it can potentially exacerbate the disparities it aims to alleviate. While a diversity office promotes the importance of individual differences, in definition, an office of "Diversity and Inclusion" focuses on creating a culture of respect, value, and belonging for all. On the other hand, an office of "Diversity and Equity" focuses on addressing the unique barriers that disadvantage a subset of students and faculty. This has important implications for students, faculty, staff, and administration. Moreover, this directly affects the perceptions of an institutions' diversity climate.